THE ROLE OF 5-HT3 RECEPTORS IN THE ANTIULCER EFFECT OF CALCITONIN - YEGEN, BERRAK (ELSEVIER SCIENCE INC, 1994)
1. The aim of the present study was to determine the role of 5-HT3 receptors of the gastroprotective effect of salmon calcitonin (sCT) and sCT-induced changes in gastric, hepatic, brain and brainstem glutathione (GSH) and lipid-peroxidation (LP) levels in rats subjected to cold-immobilization stress. 2. Stress exposure resulted in ulcer formation and a decrease in GSH levels of the liver, brain and brainstem and an increase in gastric and hepatic LP (P < 0.05). 3. sCT prevented stress-induced gastric ulcer development (P < 0.01) and reversed the decrease in hepatic and brain GSH levels (P < 0.05). 4. In the present study, a 5-HT3 receptor antagonist, ICS 205 930 was used. Interestingly, the effect of the blocker on GSH and LP levels of the tissues studied was similar to those of sCT. 5. ICS 205 930 dose dependently reversed the anti-ulcer effect of sCT although it did not antagonize the effect of sCT on GSH and LP levels, but it seemed to show an additive interaction for brain and brainstem GSH and gastric LP levels with sCT.
Keywords: RAT-BRAIN; SALMON-CALCITONIN; BINDING-SITES; SUBSTANCE-P; SPINAL-CORD; RELEASE; STRESS; CHOLECYSTOKININ; GLUTATHIONE; SECRETION